Influence of Person-Vocation Fit on Satisfaction and Persistence in Vocational Training Programs - Michaelis, Christian; Findeisen, Stefanie (Frontiers in Psychology, 2022)
Positive effects of person-environment fit on job satisfaction and persistence are well documented. However, little is known about the consequences of person-vocation (P-V) fit for vocational education and training (VET). Using data from the German National Educational Panel Study (NEPS), we examine the influence of selected P-V fit indicators (educational match, interest congruence, skill congruence) on training satisfaction and premature contract termination (PCT) for 5,646 trainees in VET. We find that as most P-V incongruences do not lead to negative consequences. Training satisfaction is not affected by interest congruence and skill congruence. However, moderate overeducation (intermediately qualified adolescents working in occupations with high shares of lowly qualified trainees) enhances training satisfaction. For PCT, there is a general effect of undereducation that is independent of educational qualification for the occupation. PCT is not affected by skill congruence and only for Realistic interests, congruence with the vocational environment reduces PCT probability.